Fermentados de macrofungos cultivados em tortas de sementes de algodão ou pinhão-manso como fontes de bioativos, enzimas e nutrientes para produção de bactérias probióticas - Cunha, Joice Raísa Barbosa (2021)
The adoption of new raw materials depends, among other things, on the commercial value of its co-products, since soybean cake market is important in the animal feed industry. Cotton and Jatropha oils have good qualities for use as biodiesel, but their residual cakes are toxic and fungal detoxification can allow its use in animal nutrition, adding value to these co-products. This study aimed to evaluate the efficiency of macrofungi (Basidiomycetes) from the collections of the Instituto Nacional de Pesquisas do Amazonas (INPA) and Embrapa Agroenergia in the detoxification of cotton seed cake (CSC) and jatropha seed cake (JSC) by solid state fermentation (SSF), as well as the bromatological characterization of these biomasses, the bioactivities of the fermented ones and the potential application as an antimicrobial and additive for animal nutrition. From 26 viable fungi, 16 of them were able to grow in the both biomasses (CSC and JSC). Four of these fungi were able to reduce the levels of phorbol esters in JSC to levels considered non-toxic (<0.09 mg/g) and at least one efficiently degraded free gossypol in CSC. The fermented macrofungi Coriolopsis sp. INPA1646 and Tyromyces sp. INPA1696 were selected for the other characterizations and their growth in CSC and JSC, respectively, resulted in increased concentrations of ergosterol, reduced antioxidant activity in these co-products and efficient production of cellulose enzymes, laccases and proteases, mainly by Tyromyces sp. in the CSC. The bromatological and structural characterization analysis showed that there was no degradation of lignin by the fungi and, therefore, did not reduce the fiber content of the biomass during the fermentation time (15 days), but confirmed its high protein concentrations and the growth of the fungi resulted in solubilization of most of these proteins. The prebiotic activity analysis of the solid and submerged fermented of these biomasses showed that the dry supernatant of unfermented JSC is more efficient than glucose, FOS and inulin in stimulating the growth of L. acidophilus, B. lactis, L. plantarum and L. rhamnosus. In addition, the submerged fermentation of CSC by Coriolopsis sp. INPA1646, Tyromyces sp. INPA1696, Panus lecomtei CC40 and Pleurotus pulmonarius EF88 made the supernatant of this biomass more efficient for the growth of L. acidophilus and the solid fermentation of JSC by these fungi produced a more efficient aqueous extract for the growth of B. lactis. About antimicrobial activity, no treatment presented an inhibition halo of enteropathogenic bacteria equal to or greater than that of Ampicillin. However, the aqueous extracts of CSC fermented by P. lecomtei CC40 and Coriolopsis sp. INPA1646, at 100 mg/mL concentration, showed inhibition halos with diameters of 1.2 and 0.73 cm, respectively, for the tested S. enterica strain. In addition, the growth supernatants of L. acidophilus, B. lactis and L. rhamnosus in the fermentation products of the biomasses were more efficient in inhibiting the growth of S. aureus than their supernatants in the control media, which indicates possible antimicrobial activity.